2005
DOI: 10.1007/s00221-004-2188-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects in feline gastrocnemius-soleus motoneurones induced by muscle fatigue

Abstract: Responses of gastrocnemius-soleus (G-S) motoneurones to stretches of the homonymous muscles were recorded intracellularly in decerebrate cats before, during and after fatiguing stimulation (FST) of G-S muscles. Ventral roots (VR) L7 and S1 were cut, and FST was applied to VR S1, a single FST session including 4 to 5 repetitions of 12-s periods of regular 40 s(-1) stimulation. Muscle stretches consisted of several phases of slow sinusoidal shortening-lengthening cycles and intermediate constant lengths. The max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 31 publications
0
20
0
1
Order By: Relevance
“…In earlier studies (Kouchtir et al 1995;Perrier et al 2000;Brizzi et al 2002;Kostyukov et al 2005) the stretch-or contraction-evoked PSPs in the spinal motoneurones were analyzed mostly qualitatively, in this study we attempted to develop quantitative approaches that could provide additional information about the naturally evoked EPSPs and their summation at the motoneuronal membrane. Slow muscle stretch evokes a great number of "miniature" EPSPs (Burke 1967); summation of the potentials leads to a steady-state membrane depolarization.…”
Section: The Stretch-evoked Epspsmentioning
confidence: 99%
See 2 more Smart Citations
“…In earlier studies (Kouchtir et al 1995;Perrier et al 2000;Brizzi et al 2002;Kostyukov et al 2005) the stretch-or contraction-evoked PSPs in the spinal motoneurones were analyzed mostly qualitatively, in this study we attempted to develop quantitative approaches that could provide additional information about the naturally evoked EPSPs and their summation at the motoneuronal membrane. Slow muscle stretch evokes a great number of "miniature" EPSPs (Burke 1967); summation of the potentials leads to a steady-state membrane depolarization.…”
Section: The Stretch-evoked Epspsmentioning
confidence: 99%
“…The main results in this field are connected with analysis of both the spike activity during artificial depolarization of the cell's membrane and the postsynaptic effects evoked by stimulation of different neural structures. Intrasomatic record from motoneurones during their natural synaptic activation presents a more difficult experimental task, although some progress in this direction is associated with recent studies with microelectrode recording from the spinal motoneurones during muscle contractions or stretches of the muscles that they innervate (Brizzi et al 2002;Kostyukov et al 2005). Controlled muscle stretches allow to model different patterns of natural activation of the motoneurones and to explore summation of a great number of EPSPs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many previous studies showed that supraspinal and spinal neural mechanisms account for the development of muscle fatigue 16,22,[24][25][26][27][28][29][30] . Decreases in descending inputs, Ia inputs from muscle spindles, and inhibitory inputs from group III and IV fibers to the MN *Correspondence: komiyama@faculty.chiba-u.jp during muscular fatigue have been proposed as potential mechanisms responsible for reducing MN excitability 22,[26][27][28]31) .…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, an academic community places greater emphasis on issues dealing with the personality traits of the cerebral processes guaranteeing the manipulation movements (MM) motorial programming. Various aspects of the abovementioned problem were studied in the area of neurophysiology of motor activities (Vasilenko, 2013;Kostykov et al, 2005; Horkovenko 2006; Kurhanskyy, Hryhal, 2010;Morenko et al, 2013;Morenko, 2014).…”
Section: Introductionmentioning
confidence: 99%